A REVIEW OF CONTROL METHODS OF WIND TURBINE SYSTEMS WITH PERMANENT MAGNET SYNCHRONOUS GENERATOR - Gajewski, Piotr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The paper presents a review of control methods of the wind energy conversion systems with permanent magnet synchronous generator. The modern vector control methods for converter system of variable-speed wind energy conversion have been described. In order to improve the energy efficiency of wind turbine, the maximum power point tracking algorithm has been applied. To verify the effectiveness of the considered configuration and its control strategy, the selected simulation studies have been performed. The obtained study results showed the high effectiveness of the considered configuration and its control methods.